Correlation between Length of Time and Sitting Position with Complaints of LBP in Students of Faculty of Medicine and Veterinary Medicine Undana - Nenoliu, Sonia; Kareri, Dyah Gita Rambu; Manafe, Derri Tallo; Setiawan, I Made Buddy (Cendana Medical Journal, 2023)
Background: Globally, the prevalence of low back pain from 1990 to 2017 varies widely, reaching 15% to 45% annually. Low back pain can be caused by bad body activity and wrong position during activities, such as a bad sitting position during activities. Sitting for a long time in the wrong position can cause side effects for students, one of the most common is lower back pain. Research Objectives: Find out the correlation between length and sitting position during online lectures with complaints of low back pain in students of the Faculty of Medicine and Veterinary Medicine Nusa Cendana University. Methods: The research method used is an analytical observational research design with a cross-sectional approach conducted on preclinical students of Medicine, University of Nusa Cendana by filling out the Roland-Morris disability questionnaire (RMDQ) and observing sitting position using the Rapid Entire Body Assessment method. (REBA) with 69 respondents from batch 2019, 2020, 2021 who have met the inclusion and exclusion criteria. The research was analyzed by univariate, bivariate using chi square test. Results: From the results of the test using the chi-square test, there is no correlation between length of sitting during online lectures with complaints of low back pain in students of Medicine, University of Nusa Cendana with p = 0.289, and there is a correlation between sitting position during online lectures with pain of lower back in students of Medicine, University of Nusa Cendana with p = 0.020. Conclusion: There is no significant correlation between length of sitting during online lectures with complaints of low back pain in students of Medicine, University of Nusa Cendana and there is a significant correlation between sitting position during online lectures with complaints of low back pain in students of Medicine, University of Nusa Cendana.